2019
DOI: 10.1002/jsfa.10092
|View full text |Cite
|
Sign up to set email alerts
|

Oil quality in sea‐level quinoa as determined by cultivar‐specific responses to temperature and radiation conditions

Abstract: BACKGROUND: There is renewed interest in quinoa as a potential source of vegetable oils; however, there is no information about how environmental conditions affect its fatty acid composition, a critical indicator of its oil quality. The fatty acid concentrations of four cultivars adapted to temperate environments were compared at three sowing dates to evaluate the effect of environmental conditions during the seed-filling period on the variation in oil quality. RESULTS: The interaction between cultivar and sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
4
15
1
Order By: Relevance
“…This effect has been extensively analysed in some crop species such as soybean (i.e. Assefa et al., 2019; Gibson & Mullen, 1996; Thomas et al., 2003; Wolf et al., 1982), although little is known about its impact on quinoa (Curti et al., 2020). In here, it was observed that seed composition changed and was especially altered in the medium‐long cycle varieties, in which high temperatures coincided with flowering and seed filling stages.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been extensively analysed in some crop species such as soybean (i.e. Assefa et al., 2019; Gibson & Mullen, 1996; Thomas et al., 2003; Wolf et al., 1982), although little is known about its impact on quinoa (Curti et al., 2020). In here, it was observed that seed composition changed and was especially altered in the medium‐long cycle varieties, in which high temperatures coincided with flowering and seed filling stages.…”
Section: Discussionmentioning
confidence: 99%
“…Quinoa seeds are gluten-free and rich in minerals, vitamins, and dietary fiber, and various bioactive compounds are also present in significant amounts in different parts of the plant. The oil content of quinoa seed ranges from 2 to 10%, with an average of 5.0–7.2% ( 3 ), with yields between 80 and 400 kg of oil ha –1 , which reveal quinoa as a new potential oilseed crop ( 9 ), although those values are lower than those found in common oilseed crops, such as sunflower (40–50%), rapeseed (30–50%), or soybean (20%) ( 10 ). Furthermore, the nutritional quality of quinoa oil is remarkable ( 3 , 4 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, variations in the chemical composition of quinoa seeds have also been reported under heat stress field conditions ( 29 , 33 ). These include changes in the fatty acid profile of quinoa, which was shown to be affected by the environmental conditions ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under tropical conditions, grains were the main nutritional source for many pre-Hispanic cultures. Nowadays, quinoa is recognized in the food industry for some of its nutritional and techno-functional properties linked to its lipidic, protein and starchy nature [6,7].…”
Section: Introductionmentioning
confidence: 99%